The sound of Ahad Analisis Semiotika dalam Film Bilal : A new Breed of Hero - Kareena Haya Prasad; Maisa Salma Fauziyah; Salma Azzahra; Zahwa Syra Wulandari; Dadan Firdaus (INDO PUBLISHING, 2026)
The animated film Bilal: A New Breed of Hero constructs an articulation locus wherein theological resilience is no longer relegated to an abstract doctrinal space; rather, it transforms into a visual representation that encapsulates the existential struggle of human nature in preserving faith beneath the grip of structured oppression. This investigation is oriented toward conceptualizing the signification of visual signs, dialogic discourse configurations, and the spectrum of symbolic elements to deconstruct the polarization between the subject's metaphysical conviction toward monotheistic principles and the socio-historical repression enforced by the Quraysh power institution, while simultaneously dissecting the phrase